Future impacts of nitrogen deposition and climate change scenarios on forest crown defoliation. - De Marco, Alessandra; Proietti, Chiara; Cionni, Irene; Fischer, Richard; Screpanti, Augusto; Vitale, Marcello (Environmental pollution (Barking, Essex : 1987), 2014)
Defoliation is an indicator for forest health in response to several stressors including air pollutants, and one of the most important parameters monitored in the International Cooperative Programme on Assessment and Monitoring of Air Pollution Effects on Forests (ICP Forests). The study aims to estimate crown defoliation in 2030, under three climate and one nitrogen deposition scenarios, based on evaluation of the most important factors (meteorological, nitrogen deposition and chemical soil parameters) affecting defoliation of twelve European tree species. The combination of favourable climate and nitrogen fertilization in the more adaptive species induces a generalized decrease of defoliation. On the other hand, severe climate change and drought are main causes of increase in defoliation in Quercus ilex and Fagus sylvatica, especially in Mediterranean area. Our results provide information on regional distribution of future defoliation, an important knowledge for identifying policies to counteract negative impacts of climate change and air pollution.
Keywords: climate change; Crown defoliation; General regression models; Nitrogen deposition; Random forests analysis

Assessing ozone and nitrogen impact on net primary productivity with a Generalised non-Linear Model. - De Marco, Alessandra; Screpanti, Augusto; Attorre, Fabio; Proietti, Chiara; Vitale, Marcello (Environmental pollution (Barking, Essex : 1987), 2013)
Some studies suggest that in Europe the majority of forest growth increment can be accounted for N deposition and very little by elevated CO(2). High ozone (O(3)) concentrations cause reductions in carbon fixation in native plants by offsetting the effects of elevated CO(2) or N deposition. The cause-effect relationships between primary productivity (NPP) of Quercus cerris, Q. ilex and Fagus sylvatica plant species and climate and pollutants (O(3) and N deposition) in Italy have been investigated by application of Generalised Linear/non-Linear regression model (GLZ model). The GLZ model highlighted: i) cumulative O(3) concentration-based indicator (AOT40F) did not significantly affect NPP; ii) a differential action of oxidised and reduced nitrogen depositions to NPP was linked to the geographical location; iii) the species-specific variation of NPP caused by combination of pollutants and climatic variables could be a potentially important drive-factor for the plant species' shift as response to the future climate change.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23078996
Keywords: Generalized Linear/non-Linear Model; Mediterranean climate; Net primary productivity; Nitrogen deposition; Ozone